Bridging the gap: linking a legacy hospital information system with a filmless radiology picture archiving and communications system within a nonhomogeneous environment...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Rubin RK; Henri CJ; Cox RD (Journal of Digital Imaging)
A health level 7 (HL7)-conformant data link to exchange information between the mainframe hospital information system (HIS) of our hospital and our home-grown picture archiving and communications system (PACS) is a result of a collaborative effort between the HIS department and the PACS development team. Based of the ability to link examination requisitions and image studies, applications have been generated to optimise workflow and to improve the reliability and distribution of radiology information. Now, images can be routed to individual radiologists and clinicians; worklists facilitate radiology reporting; applications exist to create, edit, and view reports and images via the internet; and automated quality control now limits the incidence of 'lost' cases and errors in image routing. By following the HL7 standard to develop the gateway to the legacy system, the development of a radiology information system for booking, reading, reporting, and billing remains universal and does not preclude the option to integrate off-the-shelf commercial products. Copyright (c) 1999 by W.B. Saunders Company